The Examining of Job Satisfaction Level of Koran Teachers In Terms of Some Variables - Abdulkadir Cekin (Intelektual Pustaka Media Utama, 2013)
The aim of this study is to analyze the job satisfaction level of Koran teachers. The relationships between the job satisfaction level of Koran teachers and some demographic status (gender, age and educational level) were examined. For this purpose, the Koran teachers on the sample of 243 questionnaires were selected. Statistical operations on the data obtained were analyzed via SPSS program. At the conclusion of the study, it was found that gender is the ineffective factor; educational level and age are the effective factors for job satisfaction of Koran teachers.